The Concept of Economic Development in The Thought of Selected Muslim Scholars - Saprinal Manurung (Tazkia Islamic Finance and Business Review, 2012)
Objective - Islam is a total way of life, and covers all dimensions of life. The life of the world is temporary; it is simply a transitional place before one embarks on final destination. Bearing this mind, the worldly life should be framed within Islamic paradigm, but that should not hinder Muslims to make progress and development in this temporary world as evidenced in history. During the “golden era” of Islamic civilization, Islam had produced such brilliant scientists as Ibn Hayyan (ca. 8th – 9th centuries), al-Kindi (801–873), al-Khawarizmi (ca. 8th–9th centuries), al- Battani (850–922), al-Razi (ca. 854–925/935), al-Farabi (ca. 870–950), Ibn Sina (908–946), al-Zahrawi (936–1013), Ibn Hayyan (965–1040), Omar Khayyam (1048–1131), and Ibn al-Nafis (1213–1288). In economic, Islamic civilization gave birth to scholars like al-Ghazali (1058–1111), al-Mawardi (1075–1158), Ibn Taimiyah (1263–1328), Ibn Khaldun (732-808), al-Maqrizi (1364-1442), and many others who had made great contribution to the development of Islamic economic thought.This paper is an attempt to explore the ideas and thoughts of those Muslim scholars on the concept of economic development and its relevance to the contemporary era.Method - Content AnalysisResult - Economic development is one of the objectives in achieving the welfare of the ummah and it must be based on Islamic valuesConcusions - Economic development is one of the objectives in achieving the welfare of the ummah. However, development must be based on Islamic value. Various scholars of classical and contemporary thought in the concept of development provide an opportunity for us to improve the current condition of the ummah.Keywords : Economic Development, Science and Technology, Islam, Scholar